SIKAP PETERNAK AYAM PETELUR DI JEMBER TERHADAP PAKAN PRODUKSI CHAROEN POKHPAND, JAPFA COMFEED DAN SIERRAD - Budi Pratomo Sibuea (University of Jember, 2016)
The purpose of this study was to examine the consumer’s attitudes toward layer feeds of three different brands. Data collected from 56 layer breeder in Jember. The respondents were asked to evaluate ten attributes of the products on a 5 point scale, based on Multiatribute Fishbein of The Attitude-Toward-Object Model. The result showed that the six of ten atributes of the product were evaluated to be important. Consumer’s most concerned with the availability of the product in the selection of a product. The Fishbein attitude score for Japfa Comfeed was higher than Charoen Pokhpand and Sierrad, Charoen Pokhpand was higher than Sierrad, indicating that respondents were more favorable toward Japfa Comfeed.